Pengaruh Lingkungan Kerja dan Integritas terhadap Disiplin Kerja Pegawai di Dinas Energi Sumber Daya Mineral Provinsi Sumatera Barat - Mita Apriliani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study aims to identify the significant effect of Work Environment and Integrity together with Work Discipline. This research was conducted at the Department of Energy and Mineral Resources of West Sumatra Province. This research uses associative descriptive method. The research variable uses the independent variable, namely the Work Environment and Integrity, while the variable is Work Discipline. The population of this study were employees at the Department of Energy and Mineral Resources of West Sumatra Province. because the number of samples of this population is less than 100, the number of samples in this study is the sum of the entire population of 78 employees. So that the sampling in this study is used as a whole or called total sampling. Data collection techniques in this study used a questionnaire distributed to respondents with a Likert scale measurement. The analysis of this research uses multiple linear regression test using SPSS 20.0 software. The results of the study indicate that: 1) There is a significant influence between the Work Environment on Employee Work Discipline Adjusted R Square of 0.210 and a significance value of 0.00 which means it is smaller than 0.05. 2) Integrity has a significant effect on Employee Discipline Adjusted R Square of 0.137 and a significance value of 0.01 which means it is smaller than 0.05. And 3) simultaneously Work Environment and Integrity have a significant effect on Employee Discipline Adjusted R Square of 0.268 of 0.00 which means less than 0.05.